A Portable Tunable Diode Laser Absorption Spectroscopy System for Dissolved CO(2) Detection Using a High-Efficiency Headspace Equilibrator - Zhang, Zhihao (Sensors (Basel), 2021)
Continuous observation of aquatic [Formula: see text] at the ocean surface, with a sensitive response time and high spatiotemporal resolution, is essential for research into the carbon biogeochemical cycle. In this work, a portable tunable diode laser absorption spectroscopy (TDLAS) system for dissolved CO(2) detection in surface seawater, coupled with a home-made headspace equilibrator, allowing real time underway measurements, is described. Both the optical detection part and sample extraction part were integrated together into a compact chamber. An empirical equation suitable for this system was acquired, which can convert the concentration from the gas-phase to the aqueous-phase. A monitoring precision of 0.5% was obtained with time-series measurement, and the detection limits of 2.3 ppmv and 0.1 ppmv were determined with 1 s and 128 s averaging time, respectively. Sampling device used in this work was ameliorated so that the response time of system reduced by about 50% compared to the traditional ‘shower head’ system. The fast response time reached the order of 41 s when the final concentration span was 3079 ppmv. For1902 ppmv, this figure was as short as 20 s. Finally, a field underway measurement campaign was carried out and the results were briefly analyzed. Our work proved the feasibility of the TDLAS system for dissolved CO(2) rapid detection.